Mobilizing Green Investments and PPP Governance in the Energy Transition: Regulatory Challenges and Prospects for Morocco - Mohammed Boulghalagh; Hiba Berrahal; Btissame Essafi (International Journal of Scientific Research and Innovative Studies, 2025)
The global energy transition demands a massive and urgent reallocation of capital toward low-carbon assets, crucial for achieving international climate objectives. However, mobilizing green investments unfolds within a landscape marked by multiple regulatory and institutional challenges. This article provides an in-depth analysis of the fragmentation of sustainability taxonomies, the diversity and heterogeneity of non-financial disclosure standards, and the persistent uncertainty regarding the prudential treatment of green assets. Additionally, the study highlights structural governance limitations in carbon markets, alongside non-financial constraints such as lengthy administrative permitting procedures and infrastructure bottlenecks. By comparing regulatory frameworks across the European Union, the United States, China, and Morocco, the research emphasizes that regulatory convergence, enhanced transparency, market integrity, and effective procedural reforms are essential conditions for lowering the cost of green capital and accelerating the energy transition. Lastly, the article offers strategic recommendations aimed at strengthening overall regulatory coherence and encouraging the integration of emerging economies into sustainable finance, thereby contributing to a more inclusive and effective global mechanism. Keywords: Global energy transition, green finance, sustainability taxonomies, non-financial disclosure, carbon markets, regulatory convergence, emerging economies. Received Date: July 19, 2024 Accepted Date: August 11, 2024 Published Date: August 30, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/408